Network Analysis Trough Scape and Flow Tourism Promotion in Bintan Regency - Jaya Hermawan; Evi Novianti; Awaludin Nugraha; Uud Wahyudin; Dina Oktavia (Budapest International Research and Critics University, 2022)
This study describes the concept of network through the dimensions of scape and flow. To build an analytical framework that describes the two dimensions of the network, a literature study from various sources is carried out that discusses the context of tourism promotion. This analytical framework is then elaborated through the results of in-depth interviews with twenty informants who represent the main tourism stakeholders in Bintan Regency. The informants, among others, represent elements of the government, the private sector, academia, and the community. To strengthen the analysis, especially related to the development of tourism promotion which can be directly or indirectly seen from the trend of key tourism indicators in Bintan Regency, a literature review from various books, journals, research references and online news sources from the internet is used. The Result Main finding, established networks seldom play significant role in tourism promotion as they are viewed as already settled. While tourism promotion strategy tends to inherently shows innovation, so it won’t be viewed as repetitive or redundant. This then affect engagement in post-Pandemic tourism, as shown with Bintan Regency case.